Vulnerability Assessment: Analyzing Automated Scanning Techniques for Vulnerability Assessment to Identify Weaknesses and Security Flaws in Network Infrastructure and Systems (Cybersecurity and Network Defense Research, 2024)
This research paper explores automated scanning techniques for vulnerability assessment, focusing on their role in identifying weaknesses and security flaws in network infrastructure and systems. The paper examines various automated scanning tools and methodologies, discussing their effectiveness, limitations, and best practices. The study aims to provide insights into the evolving landscape of vulnerability assessment, highlighting the importance of automated scanning in maintaining robust cybersecurity posture.